Adalimumab discontinuation in patients with early rheumatoid arthritis who were initially treated with methotrexate alone or in combination with adalimumab: 1 year outcomes of the HOPEFUL-2 study. Issue 1 (18th February 2016) - Tanaka, Yoshiya; Yamanaka, Hisashi; Ishiguro, Naoki; Miyasaka, Nobuyuki; Kawana, Katsuyoshi; Hiramatsu, Katsutoshi; Takeuchi, Tsutomu
Abstract : Objectives: To evaluate the impact of discontinuation of adalimumab (ADA) for 1 year in Japanese patients with early rheumatoid arthritis (RA). Methods: This 52-week postmarketing study, HOPEFUL-2, enrolled patients who had completed HOPEFUL-1 for early RA, in which patients received either ADA + methotrexate (MTX) or MTX alone in a 26-week randomised phase, followed by ADA+MTX in a 26-week open-label phase. Results: A total of 220 patients (ADA discontinuation: 114 patients vs ADA continuation: 106 patients) were enrolled in this study. The proportion of patients with sustained low disease activity (LDA) in the ADA discontinuation group was significantly lower than that in the continuation group (80% (64/80 patients) vs 97% (71/73 patients); p=0.001); however, most patients sustained LDA in both groups. In patients with 28-joint disease activity score (DAS28)-C reactive protein ≤2.0 at week 52, the proportion of patients who achieved sustained LDA at week 104 was 93%, suggesting that DAS28 remission may be a predictor to indicate biological-free disease control in patients with early RA. The incidence of adverse events (AE) was significantly lower in the ADA discontinuation group than in the continuation group (34.2% (39/114 patients) vs 48.1% (51/106 patients); p=0.04), most notably for infection (14.9% vs 27.4%, p=0.031). Conclusions: Although ADA discontinuation was associated with an increase in disease activity, a large proportion of patients maintained LDA with MTX monotherapy after ADA discontinuation. Since ADA discontinuation was associated with a lower AE incidence, physicians should weigh the risks and benefits of ADA discontinuation. Trial registration number: NCT01163292.